Graffiti Applications in an Interdisciplinary Context - Kucukali, Ufuk Fatih (SAUC - Street Art and Urban Creativity (repository), 2023)
Cities, which are environments of social encounter, have versatile effects on our lives as dense living spaces. One of the most important communication tools of the social environment is the street walls, which are now the public spaces of cities. This phenomenon, which belongs to the city and emerges within the framework of the city's own cycles, expresses a protest stance that reveals a new perspective with its styles, techniques, figures and conceptual dimension. In the article, the concepts of public space and art in public spaces are discussed, and graffiti, which establishes connections between different art disciplines, is defined. While the reflections of this old form of art in the contemporary world were determined, an attempt was made to understand the point reached in the evolution of graffiti as a form of expression. In particular, by examining the emergence and development processes of graffiti after 1960 and its related post-graffiti art, the most important styles, figures and techniques of graffiti have been researched, and in this context, the interdisciplinary practices of Add Fuel (Diogo Machado), Shepard Fairey, Peeta, Hozoi, Nancy Kubale, Examples of works by artists such as Zedz, Zvi Belling and Prowla, Jan Wöllert and Jörg Miedza, and Roberto Lugo are given.